Regarding One Efficient Method of Disseminating Information for Chemistry Teaching (One Example of Environmental Chemistry) - Kupatadze, Ketevan (Orbital: The Electronic Journal of Chemistry, 2021)
The article deals with methods of chemistry teaching and disseminating chemical information and focuses on the use of art. In particular, the paper describes the method of linking theatre and chemistry and widespread dissemination of chemical information. It cites an example of one specific chemical theatre show “Whirlwind of Elements”, staged by Ilia State University in 2018 and 2019, during an organized scientific picnic. The article specifies the key accents of the play, related to environmental chemistry problematics. The topics discussed are the following: quality of drinking water and water pollution with phthalates and heavy metals, air pollution and smog, acid rain. Very often, people are misinformed about chemical pollution of the environment. Some do not even know and realize that it is their action that causes the pollution. In this respect, the play highlights the human mistakes quite efficiently. It also outlines the semi-structural interview outcomes conducted with teachers, students, and representatives of other professions (non-chemists), randomly selected. The interview confirmed that the chemical emphasis in the play is placed on correct issues, and the connection between chemistry and theater ensures the right result in disseminating the information. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1472